(3EOGQI GdeHjYGJ (B/s - (3GdWGFj, MejOs ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2009)
(3EOGQI GdeHjYGJ Hjf Gdeaghe hGdJWHjb jYqO ef GdcJH GdYedjI GdJj JJfGhd HGdYQV hGdTQM hGdJhVjM BdjGJ GdHjY, caf hYde, hJbOe ddbGQF GdcQje efXhQkG ESJQGJjLjkG eJYebkG, hCOdI EQTGOjI hGVMI hObjbI, JSGYO EOGQI GdeHjYGJ aj GdefXeI Ydi UhZ GdESJQGJjLjGJ GdHjYjI GdaGYdI, hJfajPgG, heJGHYJgG, Efg cJGH eHqSW ef MjK EdJRGeg HGdeHGOF hGdCSS GdfXQjI, hGdeaGgjejI, hGdJWHjbjI, hSghdI GdWQM hGdESJbQGA hGdESJfJGL, hYeb GdJMdjd Ydi eHOC (B"(3GdSgd GdeeJfY hJHUQI eMJhjGJg cGdJGdj eONd eaGgjej dhXjaI GdHjY hGOGQI GdeHjYGJ, GdHjY GdTMUj, JfXje GdfTGW GdHjYj, WQb GdJfHD HGdeHjYGJ, GdGSJbWGH hGdGNJjGQ hJYjjf efOhHj GdeHjYGJ, JOQjH efOhHj GdeHjYGJ, GdbjGOI hGdJMajR hGdJYhjV, JMOjO aGYdjI hcaGjI COGA Gdbhi GdHjYjIs
(3HjHdjhZQGajG aj fgGjI cd aUd s
Keywords: (3GdGOGQIs; (3GdGOGQI GdYGeIs; (3GdJShjbs; (3eHjYGJs